Drought and salinity stress management for higher and sustainable canola ('Brassica napus' L.) production: A critical review - Sabagh, Ayman EL; Hossain, Akbar; Barutçular, Celaleddin; Islam, Mohammad Sohidul; Ratnasekera, Disna; Kumar, Narendra; Meena, Ram Swaroop; Gharib, Hany Sobhy; Saneoka, Hirofumi; Silva, Jaime A. Teixeira da (Australian Journal of Crop Science, 2019)
The oil of canola ('Brassica napus' L.), a globally important major oilseed crop, is used for salads, frying, the development of margarines, shortenings, and other food products. However, the growth and yield of canola are mainly restricted by drought and salinity, which can become acute in climate change. The exogenous application of some antioxidants has been shown to enhance tolerance to drought and salinity in select plants. Therefore, a thorough understanding of the effect of drought and salinity stress is crucial for understanding their adverse effect on canola cultivation and to establish useful strategies to maximize oil productivity. Given the economic importance of this crop, we reviewed studies within the extensive canola literature to assess the adverse effects of abiotic stresses, with a special emphasis on drought, water deficit and salinity, and how these stresses impact its growth and productivity in a bid to determine the role that antioxidants might play in alleviating the adverse effects of environmental stresses. This review notes how the productivity of canola tends to decrease under different abiotic stresses due to their adverse effect on morphological, physiological and biochemical processes, including lowered or reduced leaf area, leaf relative water content, stability of cell membranes, photosynthetic capacity, stomatal conductance, damage to chlorophyll and the production of reactive oxygen species. In addition, this review also discusses management strategies that would allow researchers or farmers to mitigate salinity and drought stress by using compatible solutes, nutrient management or other means to maximize canola yield. The application of antioxidants to soil, in combination with essential nutrients, alongside other management strategies, may assist in alleviating the harmful effects of environmental stresses in canola production.